Forty Years Without Luria With Luria - Glozman, J (KnE Life Sciences, 2018)
The article compares five Luria International Memorial Congresses in Russia and some Luria Memorial Conferences abroad to prove the intensive and extensive development of Lurian approach. Such a development was assured by Lurian international school of psychologists (his colleagues, disciples and followers) who work or worked in different branches of psychology. The Lurian approach or Lurianism is defined as a combination of systemic and cultural-historical approaches. The specific Lurian approach in neuropsychology is determined by its subjects’ orientation. It means, that the Lurian neuropsychological analysis is not centered on a disease (its symptoms and severity, functional and cognitive disturbances), but on a subject: his personal experience, health concepts, coping strategies and attitudes, social interactions and so on. Lurian neuropsychology is a ‘unified theory of cerebral and mental functions’. It explains why Lurianism still rests a source for development of both fundamental and applied psychology. Keywords: Luria International Memorial Congresses, Lurianism, systemic and cultural– historical approaches